Child disruptiveness moderates the effects of home book reading on oral language development. (October 2022) - Laursen, Brett; Hoff, Erika; Gaudree, Aerdin; Højen, Anders; Bleses, Dorthe
Abstract: Pediatricians recommend that parents read aloud to children, on the assumption that book reading during early childhood promotes language skills. However, it is not clear that children similarly profit from the practice, particularly those whose behavioral tendencies interfere with processes that leverage supportive environmental experiences into language gains. Participants in this two-wave longitudinal cohort study were 546 (282 boys, 264 girls) 4–5 year-olds enrolled in 24 population-based childcare centers in 13 municipalities across Denmark. Teachers administered standardized assessments of child language skills twice, approximately 6 months apart. At the outset, parents reported the frequency an adult read books to the child at home, and teachers assayed child conduct problems and hyperactivity. Results indicated that home book reading benefits were not uniformly distributed. Book reading predicted improvements in communication skills (β = 0.74) and language comprehension (β = 0.31), with the strongest effects for children with above average conduct problems (β = 0.88 to 1.72) and those with below average hyperactivity (β = 1.35). Highlights: Child characteristics moderate the relation between home book reading and oral language growth. Book reading is particularly beneficial for children with conduct problems. The absence of home book reading particularly disadvantages children with conduct problems.. Hyperactivity hampers the child's ability to profit from home book reading.